RESULTS OF USING SUSTAINABLE AVIATION FUEL IN TRANSPORT AIRCRAFT ON DIFFERENT FLIGHT LEVELS AND THEIR INFLUENCE ON CARBON-DIOXIDE CO2 EMISSIONS - Dragan LAZIC; Vladimir GRUJIC; Dragan CVETKOVIC (Scientific Journal of Silesian University of Technology. Series Transport)
During the recent 40 years, the quantity of energy sources globally has been reduced, and the consequence of this situation that the oil in the world becomes more expensive. Many manufacturers have been forced to initiate the development of completely new concepts of developing commercial aircraft which would be more rational regarding fuel consumption by completely retaining the best quality of passenger services. A continuous uptrend of the propellant cost globally since 1990s has forced not only smaller companies but also the most powerful enterprises in aviation industry, such as the “General Electric”, to return to the research and development programs of Turbo Prop engines. In the case of the aircraft DHC Dash 8 Q 400, the engineering preparation of the flight for calculating the changes of travel propellant while the switch of the flight altitude was being done. By analyzing nine various levels of flight, the conclusion has been indisputably reached that regardless of the vast altitudes of a flight and the horizontal distance covered during climb and descent, the fuel consumption is significantly lower than while flying at much lower altitudes with much lower horizontal distance in climb and descent. All the indicators that have been reached undeniably confirm the fact that a flight at great altitudes enables lower consumption of fuel and less necessary time of the flights. By such analysis and setting sustainable aircraft fuels into equations, numerous improvements in the world of aviation, which directly influence the quality of life on the global level, are achieved. Likewise, it will indicate the possibility of substitution of classical hydrocarbon (fossil) fuels with biofuels which, while burning, release much lower emission of exhaust gases.